2020
DOI: 10.1108/bfj-08-2020-0755
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the antecedents of e-commerce satisfaction in social commerce context

Abstract: PurposeSocial media is still influencing consumers and is extending social commerce (S-Commerce) use. Different social media activities can influence the users' trust and e-satisfaction at different levels, which in turn influence the purchase intentions. This is evident for the food and beverage industry as S-Commerce mediated by social media can help realise a shorter time to market and meet buyer demands. In addition, credibility factors may influence trust and purchase intentions. Understanding the various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 76 publications
5
63
0
20
Order By: Relevance
“…[51] identified a positive connection between ecommerce satisfaction and spending. Reference [52] demonstrated that trust influences ecommerce satisfaction, leading to purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[51] identified a positive connection between ecommerce satisfaction and spending. Reference [52] demonstrated that trust influences ecommerce satisfaction, leading to purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Satisfaction encourages creating an improved relationship between consumers and social media platforms. This enhanced relationship will motivate users to write better feedback and spread positive word-of-mouth which reflects how satisfied the user is [88,91,92]. Hence, increasing users' satisfaction levels is crucial for social media sites [93].…”
Section: Satisfaction and Continuous Intention To Usementioning
confidence: 99%
“…Electronic word-of-mouth also significantly affects purchase intention. Attar et al (2020) [12] conducted a study titled Investigating the Antecedents of E-Commerce Satisfaction in Social Commerce Context and found that trust significantly affects e-commerce satisfaction leading to purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%